Insight into rotational effects on a horizontal axis wind turbine NREL phase II using CFD simulation and inverse BEM - Belamadi, Riyadh; Mdouki, Ramzi; Adrian, IlincaIlinca; Djemili, Abdelouaheb (جامعة الوادي - university of el oued, 2017)
The present work aims to study the aerodynamic characteristics of the NREL phase II rotor (generated only with S809 profile along the span for an untwisted case) that is a horizontal axis downwind wind turbine rotor and which is assumed to stand isolated in the space. The threedimensional steady-incompressible flow Reynolds Averaged Navier-Stokes equations are solved by using the commercial CFD package ANSYS FLUENT and, the turbulence closure model k-ω with shear stress transport correction was adopted for all computations. The computations were done for wind speed of 7.2, 10.56, 12.85, 16.3, and 9.18 m.s-1. Results of pressure and torque for considered wind turbine rotor have been directly compared to the available experimental data. The comparisons show that CFD results along with the turbulence model can predict the spanwise loading of the wind turbine rotor with reasonable agreement. Secondly, A comparison of lift and drag coefficients was made between the results obtained using the inverse algorithm BEM based on the calculated pressure distributions and the experimental test data. The result show that the general trend is similar for all sections of the scale, however, large deviation exists between the 2-D and 3-D case
Article
Keywords: CFD computation, RANS, Horizontal axis wind turbine, inverse BEM, Rotational effect, turbulent flow.